Selective ROCK2 inhibition in focal cerebral ischemia. (19th November 2013) - Hyun Lee, Jeong; Zheng, Yi; von, Daniel; Wei, Ying; Balcioglu, Aygul; Daneshmand, Ali; Yalcin, Nilufer; Yu, Esther; Herisson, Fanny; Atalay, Yahya B.; Kim, Maya H.; Ahn, Yong‐Joo; et al.
Abstract Objective Rho‐associated kinase (ROCK) is a key regulator of numerous processes in multiple cell types relevant in stroke pathophysiology. ROCK inhibitors have improved outcome in experimental models of acute ischemic or hemorrhagic stroke. However, the relevant ROCK isoform (ROCK1 or ROCK2) in acute stroke is not known. Methods We characterized the pharmacodynamic and pharmacokinetic profile, and tested the efficacy and safety of a novel selective ROCK2 inhibitor KD025 (formerly SLx‐2119) in focal cerebral ischemia models in mice. Results KD025 dose‐dependently reduced infarct volume after transient middle cerebral artery occlusion. The therapeutic window was at least 3 h from stroke onset, and the efficacy was sustained for at least 4 weeks. KD025 was at least as efficacious in aged, diabetic or female mice, as in normal adult males. Concurrent treatment with atorvastatin was safe, but not additive or synergistic. KD025 was also safe in a permanent ischemia model, albeit with diminished efficacy. As one mechanism of protection, KD025 improved cortical perfusion in a distal middle cerebral artery occlusion model, implicating enhanced collateral flow. Unlike isoform‐nonselective ROCK inhibitors, KD025 did not cause significant hypotension, a dose‐limiting side effect in acute ischemic stroke. Interpretation Altogether, these data show that KD025 is efficacious and safe in acute focal cerebral ischemia in mice, implicating ROCK2 as the relevant isoform in acute ischemic stroke. Data suggest that selective ROCK2 inhibition has a favorable safety profile to facilitate clinical translation.